Efficiency of Service Providing Enterprises Increase Issues (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article contains ways to use resources efficiently in service companies. In addition, the features of the service efficiency are analyzed, the dynamics of service networks, the dynamics of economic growth in the industries and the effective development of service networks.